Determining the International Hub Port on Sumatra Island Using the Integration of Geographic Information System and Analytical Hierarchy Process Methods - Setijadi, Setijadi; Hartati, Verani; Fauzi, Muchammad; Salma, Melati (Spektrum Industri, 2025)
Indonesia’s maritime trade development heavily depends on the effective utilization of its port infrastructure, particularly in Sumatra, which is strategically located along the Malacca Strait and near major ASEAN markets. However, trade and logistics activities remain concentrated in Java, creating regional imbalances and leaving western Indonesian ports underutilized. This study aims to identify the most strategic ports in Sumatra that can serve as international trade hubs by developing a spatially integrated, multi-criteria evaluation framework. Three main criteria, trade volume, global connectivity, and multimodal accessibility, were assessed using the Analytic Hierarchy Process (AHP) based on expert input from port management, logistics, and transport planning specialists. Geographic Information System (GIS)-based proximity analysis was applied to evaluate each port’s access to roads, railways, and industrial centers, producing a Multimodal Connectivity Index integrated into the AHP model. The findings reveal that Boom Baru (Palembang), Belawan (Medan), and Batu Ampar (Batam) rank as the top-performing ports, with final scores of 0.875, 0.855, and 0.800, respectively. These ports exhibit high trade volumes and superior multimodal connectivity, with Boom Baru and Belawan achieving the highest connectivity index (2.67 out of 3.00). In contrast, Pekanbaru and Tanjung Balai Karimun scored lower due to limited infrastructure and weaker integration. The study concludes that incorporating GIS-based spatial analysis into the AHP framework reduces subjectivity in port evaluation and provides a replicable, data-driven tool for regional infrastructure prioritization. This approach contributes a novel composite index and offers strategic insights for developing Sumatra’s role in Indonesia’s maritime trade network.